Aditivos naturais na conservação de carcaças de codornas Européias (coturnix coturnix coturnix) - Dias, Francisca Kelia Duarte (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this work was to evaluate the use of natural extracts (oregano extract and propolis extract) and organic acid lactic acid as an alternative for the hygiene and conservation of European quail carcasses, aiming to increase shelf life and better quality sense of the flesh. The carcasses were evaluated based on the chemical characteristics (moisture, proteins, fat, ash and lipid oxidation), physical (water retention capacity-CRA, post-cooking weight loss, texture, pH and instrumental color) (coliforms at 44 ° C, psychotropic bacteria, aerophilic mesophilic bacteria, coagulase-positive staphylococci and Salmonella sp.). The results obtained in this work indicate that the use of oregano extract and propolis extract can be considered viable alternatives in the control of microbial growth and maintenance of the physical, chemical and sensorial characteristics of the product during the shelf life, when compared to the control group and the treatment using lactic acid at 2%
Keywords: Extrato; Qualidade de carne; Aceitabilidade; Extract; Meat quality; Acceptability; CIENCIAS AGRARIAS::MEDICINA VETERINARIA